Reproductive system and molecular variations of Jatropha curcas L. accessions - Noor Alam, Noor Camellia (2012)
Three studies were conducted to describe microscopically the flowering and fruit set,pollination ecology and genetic relationships and variations of Jatropha curcas L. accessions in Malaysia. For the first study, investigations were carried out by observing the floral morphology, flowering sequence of pistillates, floral anthesis time, flower daily anthesis, flowering and fruiting behaviour pattern, flower sex and fruit set ratio of Jatropha curcas. The organogenesis of the floral reproductive organs was examined using Scanning Electron Microscope (SEM). Jatropha is a monoecious plant and produces individual flowers in a dichasial cyme. Each Jatropha inflorescence has at least six compound dichasium. Jatropha flowers are pale green in colour with only a difference in sepal length between the male and female flowers. The flowering sequence of the female flowers in Jatropha begins at the upper most terminal of the inflorescence and simultaneously on the upper most terminal of the lowest cyme tier and this is followed by other cyme tier in the inflorescence for the second day of flowering. Male flower anthesis started the earliest at hour 0000 and again at hour 0610-0646 while the female flower anthesis commenced at 0635-0825. Male flowers anthesis was for a period of 8-11 days, while female flowers opened for only 3-4 days. Two observations on flower sex and fruit set ratio were done at different flowering season in December 2008 and April 2009. The reading of the male to female flower ratio was 22: 1 in December 2008 and 27: 1 in April 2009. The flower to fruit ratios were 6: 5 (January 2009) and 2: 1 (May 2009). Numerically, 0-10 female flowers and 25-215 male flowers are produced in the same inflorescence. In this study, the terminal stem of Jatropha bears fruits profusely in January, May and August 2009. In March, June and October, flowering took place after the vegetative stage. Development of the floral meristem consists of three stages that include a vegetative stage, transition from vegetative to floral stage and the development of flower parts. The meristem was in the transition stage at day 6. All sepals and a petal were developed at day 18 but there was no presence of reproductive organs developing at this stage. Flower and fruit development takes approximately 100 days to complete the cycle from the initiated floral bud stage until fruit maturity. Continuous flowering on the same inflorescence and the incidents where flowering terminated in the middle of the flowering period were factors believed to cause the wide range of fruit ripening times recorded. The problem of small number of fruits produced in Jatropha curcas is mainly caused by the small number of pistillate flowers present in each inflorescence that range from 0 to 10 flowers in the each inflorescence. Jatropha could have two to four cyclical fruiting peaks in Malaysia. For the second study, investigation was carried out by observing the flower visitors behaviour based on the duration of each visit by an insect species, mean abundance, the peak hour of visitation, and the rate of visitation during 5 min periods (number of visits/min) throughout the day (24 hours) for ten plants. Eight insect species were found to visit Jatropha curcas flowers in this study which is Monomorium pharaonis L., Monomorium minimum, Lasius niger, Apis cerana, Lucilia sp., Anomala pallid, Blattela germanica and Hexacentrus unicolor. Ant species; Monomorium pharaonis, Monomorium minimum and Lasius niger can be found abundantly at Jatropha flowers which contribute 92% of overall visitation. More than one individual species were observed visiting the flowers at a time except Hexacentrus unicolor. The numbers of insect visited male flowers (786 visits) were almost three times more than on female flowers (295 visits).The rate of visitation was almost two visits per minute per inflorescense. Apis cerana is the fastest among all species to visit Jatropha flowers which spent one to five seconds and observed robbing the Jatropha pollens. It visited male flowers at hour 0830 to 1400 and visited female flowers at hour 1300 to 1400. All species of ants and flies were only visiting for nectars. Monomorium pharaonis L. can be observed abundantly at most of the time from early morning till midnight to rob nectar. The study revealed that Monomorium pharaonis, Monomorium minimum, Lasius niger and Apis cerana can be considered as effective pollinators for Jatropha curcas with regard to the duration of visits and abundancy. The peak hour of visitation occurred during the day which around 0830 till 1830 right after the flower anthesis took place. This situation promotes pollination to the maximum point as insect pollinators can be found abundantly after the flower anthesis. For the third study, the experiment was undertaken to assess the extent of genetic diversity in a representative set of 16 accessions of Jatropha curcas. Inter-simple sequence repeat (ISSR) analysis was used to establish the genetic relationship among the accessions. Only six ISSR primers UBC812, UBC834, UBC847, UBC880, I1 and I2 generated a polymorphic banding profile out of 8 primers used. The number of amplicons per primers varied from 6 (UBC812) to 14(UBC834) and the amplicon size from 151 bp to 2779 bp. Out of a total of 55 bands, 25 (45.45%) were polymorphic with an average of 4.16 polymorphic bands per primer. Jaccard’s coefficient of similarity varied from 0.72 to 1, indicating low level of genetic variation among the studied genotypes. The similarity was found to be the lowest (0.72) between accessions from Kelantan and Selangor while the highest (1.0) was between accessions from Sabah and Brunei. UPGMA cluster analysis indicated six main clusters at a threshold of 90% with the highest number of accessions grouped under cluster II. Although, the grouping was not related to location sources, there was a close genetic relationship among the Jatropha accessions represented. The low degree of variation represented maybe mainly attributed to the fact that J.curcas is an introduced plant species in Malaysia and comes from the same source when they were introduced to Malaysia and most likely the source was to be Indian as two of the accessions (I & M) were from India. The variation also can low due to the low number of markers used in the study.